Hazard assessement of metallic nanomaterials in human respiratory cells - Saruga, Andreia (2018)
As the applications of nanomaterials (NM) have been exponentially increasing, serious concerns about their potential impact on human health have been raised and challenging questions to regulators came up. This work investigated the toxicity of widely used metallic NM, namely cerium dioxide (CeO2, NM-212), titanium dioxide (TiO2, NM-100 and NM-101) and barium sulphate (BaSO4, NM-220). A standardized protocol for NM dispersion was followed and the quality of the dispersion in the culture medium was evaluated by dynamic light scattering. A human alveolar cell line (A549) was exposed to 1-100 μg/cm2 of each NM for cytotoxicity (MTT and clonogenic assays) and genotoxicity (comet and micronucleus assays) assessment. A decrease in cells’ proliferative capacity was detected after exposure to the two highest concentrations of CeO2 for 7 days (p=0.01 and p=0.002, respectively) while the remaining NM were not cytotoxic. Concerning genotoxicity, TiO2 NM significantly increased the level of DNA breaks but those lesions seemed to be efficiently repaired because no chromosome instability was detected by the micronucleus assay. The CeO2 NM induced a two-fold (non-significant) increase of in the level of oxidative DNA. BaSO4 NM was neither cytotoxic nor genotoxic under the tested conditions. Although the present results contribute to the risk assessment of these NM, the real effects from human exposure, e.g., in the workplace, are still unclear. Thus, the implementation of high throughput methodologies to allow cost-efficient strategies and experimental models that better mimic in vivo responses is an urgent need to allow nanosafety studies to keep pace with innovation.